Bordetella pertussis autotransporter Vag8 binds human C1 esterase inhibitor and confers serum resistance. - Nico Marr; Nita R Shah; Rose Lee; Emma J Kim; Rachel C Fernandez (PLoS ONE, 2011)
Bordetella pertussis employs numerous strategies to evade the immune system, including the ability to resist killing via complement. Previously we have shown that B. pertussis binds a complement regulatory protein, C1 esterase inhibitor (C1inh) to its surface in a Bvg-regulated manner (i.e. during its virulence phase), but the B. pertussis factor was not identified. Here we set out to identify the B. pertussis C1inh-binding factor. Using a serum overlay assay, we found that this factor migrates at approximately 100 kDa on an SDS-PAGE gel. To identify this factor, we isolated proteins of approximately 100 kDa from wild type strain BP338 and from BP347, an isogenic Bvg mutant that does not bind C1inh. Using mass spectrometry and bioinformatics, we identified the autotransporter protein Vag8 as the putative C1inh binding protein. To prove that Vag8 binds C1inh, vag8 was disrupted in two different B. pertussis strains, namely BP338 and 18-323, and the mutants were tested for their ability to bind C1inh in a surface-binding assay. Neither mutant strain was capable of binding C1inh, whereas a complemented strain successfully bound C1inh. In addition, the passenger domain of Vag8 was expressed and purified as a histidine-tagged fusion protein and tested for C1inh-binding in an ELISA assay. Whereas the purified Vag8 passenger bound C1inh, the passenger domain of BrkA (a related autotransporter protein) failed to do so. Finally, serum assays were conducted to compare wild type and vag8 mutants. We determined that vag8 mutants from both strains were more susceptible to killing compared to their isogenic wild type counterparts. In conclusion, we have discovered a novel role for the previously uncharacterized protein Vag8 in the immune evasion of B. pertussis. Vag8 binds C1inh to the surface of the bacterium and confers serum resistance.